“Are We a Bunch of Robin Hoods?”: Filesharing as a Folk Tradition of Resistance - Staple, Benjamin (Ethnologies, 2019)
On the edge of the digital frontier, far from the oceans of their maritime namesakes, pirate communities flourish. Called outlaws and thieves, these file-sharers practice a vernacular tradition of digital piracy in the face of overwhelming state power. Based on ethnographic fieldwork conducted with Warez Scene cracking groups and the Kickass Torrents community, this article locates piracy discourse as a site of contested identity. For file-sharers who embrace it, the pirate identity is a discursively-constructed composite that enables users to draw upon (and create) outlaw folk hero traditions to express themselves and affect small-scale change in the world around them. This article argues that pirate culture is more nuanced than popularly depicted and that, through traditional practice, piracy is a vernacular performance of resistance.